Understanding the nose–brain axis and its role in related diseases: A conceptual review - Mou, Ya-Kui; Song, Xiao-Yu; Wang, Han-Rui; Wang, Yao; Liu, Wan-Chen; Yang, Ting; Zhang, Ming-Jun; Hu, Yue; Ren, Chao; Song, Xi-Cheng (Neurobiology of disease, 2024)
The nose–brain axis (NBA), a critical component of the body–brain axis, not only serves as a drug transport route for the treatment of brain diseases but also mediates changes such as neuroimmune disorders, which may be an important mechanism in the occurrence and development of some nasal or brain diseases. Despite its importance, there are substantial gaps that remain in our understanding of the characteristics of NBA-mediated diseases and of the cellular and molecular mechanisms underlying the bidirectional NBA crosstalk. These gaps have limited the translational application of NBA-related research findings to some extent. Therefore, this review aims to address the conceptual framework of NBA and highlight its values in representative diseases by combining existing literature with new research results from our group. We hope that this paper will provide a basis for further in-depth research in this field, and facilitate the clinical translation of NBA.